Profile of Maxillofacial Fracture Patients at General Hospital in Surabaya - Bonfilio Neltio Ariobimo; Marjono Dwi Wibowo; Abdurachman Abdurachman (Biomolecular and Health Science Journal, 2021)
Introduction: Maxillofacial fractures can be caused by blunt trauma or sharp trauma. The purpose of this study was to identify the characteristics in patients with maxillofacial fractures who were treated in the Head and Neck Surgery Division of Dr. Soetomo General Academic Hospital, Surabaya during 2016.Methods: The research design was cross-sectional from patients with maxillofacial fractures. Those variables were evaluated are gender, age, type of etiology, site of maxillofacial fracture, gender and type of etiology based incidence, age and type of etiology based incidence. Data presented descriptively.Results: From 68 patients, consisted of 57 (83.82%) male, average age of 30.1 years old. The most common type of etiology was traffic accidents (92.64%), most common site of fractures were mandibular (33.33%), gender associated with the type of etiology was men who experienced traffic accidents (79.41%), and the age associated with the most types of events was ages 26-45 years with traffic accidents (47.05%).Conclusion: Maxillofacial fractures still become the problem that mainly cause is traffic accidents which occurred mostly in male and mandibular fracture as the most common site of fracture.